The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852 - Laurent, Ryan A. St; Giusti, Alessandro; Mielke, Carlos G. C. (Zootaxa, 2018)
In order to clarify the identity of the type species of one of the most diverse Mimallonidae genera, Cicinnus Blanchard, 1852, we designate a lectotype for Cicinnus orthane Blanchard, 1852 with photographs of the lectotype (dorsal and ventral) and its genitalia figured for the first time. Cicinnus orthane, described from Chile, is a close morphological match for a southeastern Brazilian species, which we also illustrate for comparative purposes. Because the lectotype of C. orthane is female, we include both sexes of this related Brazilian species in order to facilitate the figuring of male genitalia as well as comparisons of the female genitalia. We are therefore able to establish sound morphological characteristics for Cicinnus sensu stricto, namely in the males the bifid configuration of the gnathos, a complex juxtal arrangement fused to the phallus, and largely membranous valvae; and in the females a wide and narrow lamella antevaginalis, lack of setae covered bulbous masses on either side of the lamella antevaginalis, well-sclerotized and posteriorly protruding tergite VIII, and reduced, stout apophyses anteriores which are about one quarter the length of the apophyses posteriores.